Evolution of the Aza-Diels–Alder Reaction of 2H-Azirines - Zhou, Hao; Shen, Mei-Hua; Xu, Hua-Dong (Synlett, 2016)
The aza-Diels–Alder reaction of 2H-azirines with 1,3-dienes provides facile access to the structurally intriguing and difficult to access 1-azabicyclo[4.1.0]hept-3-ene scaffold. Its application in organic synthesis and medicinal chemistry is heavily hampered by the narrow substrate scope for both reacting partners. Herein, the discovery and exploration of this reaction are summarized and discussed. A recent breakthrough is an intramolecular version that overcomes the limitations of conventional methods.
Keywords: aza-Diels–Alder reaction; 2H-azirines; vinyl azide; intramolecular Diels–Alder reaction; N-heterocycles